Prinsip Keadilan Ditinjau dari Hukum Islam dalam Kehidupan Bermasyarakat - Muhamad Habib; Dinda Aurellia Intan Pramesti Cahyani; Naila Cahaya Putri; Ma’Uzia Az-Zahro; Lutfiansyah Adam Gusma; Sapta Hadi Aditia Wardana (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2026)
Justice is a fundamental principle in Islamic law that plays an essential role in regulating social life and maintaining harmony within society. This study aims to examine the implementation of the principle of justice in Islamic law in the social, economic, and legal aspects of society. The research employs a normative legal approach by analyzing primary legal sources, namely the Qur'an and Hadith, as well as relevant books, journal articles, and other scholarly literature. The findings indicate that justice in Islamic law is universal, comprehensive, and applicable to various dimensions of human life, including economic transactions, law enforcement, inheritance distribution, and the protection of individual rights. The implementation of this principle is intended to create balance, social welfare, legal certainty, and mutual respect among community members. However, several challenges continue to hinder its effective application, including social inequality, abuse of authority, weak law enforcement, limited public understanding of Islamic legal values, and inconsistencies in implementing legal principles. Therefore, stronger commitment and collaboration among governments, legal institutions, religious leaders, educators, and society are needed to promote and actualize the values of justice in accordance with Islamic teachings, thereby fostering a more equitable, peaceful, and prosperous society.